Multicultural-Based Values at SMA Don Bosco Padang - Zeri Milyuta Putra (LANGGAM: International Journal of Social Science Education, Art and Culture, 2024)
This research aims to explore the role of multicultural education at Don Bosco High School in Padang and its impact on students' inclusive attitudes towards cultural and religious diversity. In the context of globalization, the importance of education that promotes understanding and appreciation of differences is increasingly recognized. The study also aims to analyze the implementation of multicultural values in the curriculum of Don Bosco High School Padang, evaluate students' participation in social activities reflecting multicultural values, and assess its impact on students' inclusive attitudes. The research adopts a descriptive qualitative case study approach. Data were collected through interviews with teachers and students, school activity observations, and document analysis, focusing on the educational reports of the year 2023. The research findings indicate that Don Bosco High School Padang has successfully integrated multicultural values into its curriculum. Teachers play a mentoring role, guiding students in academic and personal development. Student participation in social activities reflects multicultural values, promoting intercultural dialogue. Holistic emotional support is implemented, encompassing academic, career, and personal development aspects. In conclusion, this research suggests that Don Bosco High School Padang has taken positive steps in creating an inclusive environment that encourages understanding and appreciation of cultural and religious diversity. Research recommendations include ongoing efforts to enhance tolerance and support for religious and cultural equality.